Hubungan Tingkat Pengetahuan dengan Perilaku Pencegahan Gastroesophageal Reflux Disease (GERD) di Puskesmas Kecamatan Mampang Prapatan - Hisyami, Siti Nurpaidiah; Panjaitan, Ribka Sabarina; Rizqa Wahdini (JURNAL KESEHATAN PRIMER, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is a digestive tract disorder caused by gastric acid reflux that causes typical symptoms, such as heartburn and regurgitation. Unhealthy lifestyle and diet are the main risk factors for GERD. Therefore, it is important to identify knowledge and behavior factors as preventive components. Objective: To determine the relationship between the level of knowledge and GERD prevention behavior at the Mampang Prapatan District Health Center. Method: This study used a descriptive correlation design and a cross-sectional approach. The sample of this study was 97 respondents with a history of GERD, taken using a total sampling technique. Data collection used a questionnaire and was analyzed using the Fisher-Freeman-Halton Exact Test. Results: The results showed that 80.4% of respondents had good knowledge and 47.4% showed good prevention behavior. Statistical tests showed a p-value <0.001, which indicates a significant relationship between the level of knowledge and GERD prevention behavior. Conclusion: A good level of knowledge has a positive effect on GERD prevention behavior. This study emphasizes the importance of developing health education, both directly and through digital media, to increase public awareness of preventive behaviors and improve the quality of life of GERD sufferers in a sustainable manner.